A total production system study on Republic-Asahi Glass Corporation - Dimaano, Jed P. (College of Engineering, 1996)
Republic-Asahi Glass Corporation is a joint venture between Asahi Glass Co Ltd., one of the world's leading flat glass producers, and Republic Glass Holdings Corporation, the pioneering flat glass company in the Philippines. Although RAGC was already ISO 9002 certified by the Bureau of Product Standards, system improve met is still their top priority. They would have to produce quality products at lower costs. This paper is a study of one of the top manufacturing expenses of RAGC - Packaging materials. The company has been spending a considerable amount of money in unneeded inventory leading to insufficient storage space and high opportunity costs. The team investigated on the inventory control system of the Packaging Department and was able to develop a more systematic control of finding the most appropriate level that would prevent overstocking and stock-outs. Historical data was used to justify the claims. In a monopolistic business nature like that of RAGC, customer satisfaction may be considered as something that needs no special attention since it does not elicit an immediate opportunity cost. However, in its pursuit of maintaining its stature in the glass industry and its ultimate ideal of continuous improvement, customer dissatisfaction may also be a cost that should be taken into consideration. Republic-Asahi had meeting delivery dates as one of their main problems. Most of their delivery requirements were not met due to the unavailability of delivery trucks. Trucks were not available either due to excessive service time in the distributor or refusal to deliver due to low pay or simply inefficiency. IT was therefore recommended that the delivery pay be increased to market price, waiting time for unloading to be eliminated, a daily order forecast be made, and that a more efficient and systematic scheduling program be devised. The recommendations made were basically just improvements of the existing system. therefore, no drastic changes were suggested and thus, no significant costs were involved.